Smart pest management through IoT and AI interventions$ - Rameash, K (Indian Journal of Plant Protection, 2025)
Modern innovations in advanced computing devices and expanding horizons of information and communication tools have changed the way of crop pest monitoring and management. The availability of wireless sensors, unmanned aerial vehicles, global positioning systems, robotic devices, cloud-based solutions and affordable internet connectivity provides a huge opportunity to devise an early detection of insect, disease and weed infestations and formulate appropriate pest management strategies. Some of the technologies like computer vision, machine learning, artificial intelligence (AI), mechatronics and actuators are being currently adopted for precision agriculture and have potential applications in smart pest monitoring, management and forecasting. With the help of these technologies, the cost involved in laborious pest surveillance can be curtailed and the application of a huge volume of chemical pesticides use can be reduced, which would result in reduced cost of pest management, sustained environment along with enhanced productivity.